2012
DOI: 10.1167/iovs.12-9662
|View full text |Cite
|
Sign up to set email alerts
|

TheRd8Mutation of theCrb1Gene Is Present in Vendor Lines of C57BL/6N Mice and Embryonic Stem Cells, and Confounds Ocular Induced Mutant Phenotypes

Abstract: These findings identify the presence of the rd8 mutation in the C57BL/6N mouse substrain used widely to produce transgenic and knockout mice. The results have grave implications for the vision research community who develop mouse lines to study eye disease, as presence of rd8 can produce significant disease phenotypes unrelated to the gene or genes of interest. It is suggested that researchers screen for rd8 if their mouse lines were generated on the C57BL/6N background, bear resemblance to the rd8 phenotype, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
514
3
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 596 publications
(545 citation statements)
references
References 10 publications
17
514
3
2
Order By: Relevance
“…As reported by Mattapallil et al, 17 the rd8 mutation in the Crb1 gene is found in the C57BL/6N substrain but not in the C57BL/6J substrain. This mutation results in ocular spots and retinal lesions such as retinal folding, dysplasia of the nuclear layers, retinal degeneration, and vacuolation of the retinal pigment epithelium.…”
Section: Rd8 Mutationsupporting
confidence: 66%
See 1 more Smart Citation
“…As reported by Mattapallil et al, 17 the rd8 mutation in the Crb1 gene is found in the C57BL/6N substrain but not in the C57BL/6J substrain. This mutation results in ocular spots and retinal lesions such as retinal folding, dysplasia of the nuclear layers, retinal degeneration, and vacuolation of the retinal pigment epithelium.…”
Section: Rd8 Mutationsupporting
confidence: 66%
“…Mattapallil et al 17 showed that a series of commercially available ES cells of C57BL/6N origin and C57BL/6N mouse lines used to generate ES cells contained the rd8 mutation in the Crb1 gene. This mutation results in a form of retinal dysplasia and degeneration.…”
Section: Southern Blot Analyses For Isolation Of Targeted Es Cell Clonesmentioning
confidence: 99%
“…Chimeric mice were mated to 129/SvEv mice, and the colony was maintained in C57/129 mixed background. The C57BL/6N strain carries the Crb1 rd8 mutation (43), and the rd8 mutation was eliminated by breeding. Lztfl1 genotype was determined by PCR, using the following primers: F-common: TAA-CAT-GCC-ACT-TGG-ACA-TCA-TGG, R-WT: ATT-CCA-TGA-AAG-CTG-GTG-TTG-TGA, and R-Mut: CCA-CAA-CGG-GTT-CTT-CTG-TTA-GTC.…”
Section: Methodsmentioning
confidence: 99%
“…Lztfl1 genotype was determined by PCR, using the following primers: F-common: TAA-CAT-GCC-ACT-TGG-ACA-TCA-TGG, R-WT: ATT-CCA-TGA-AAG-CTG-GTG-TTG-TGA, and R-Mut: CCA-CAA-CGG-GTT-CTT-CTG-TTA-GTC. Bbs1 M390R knock-in mice and rd8 genotyping were previously described (27,43).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, they were free of the rd8 mutation by PCR analysis. 55 129/SvImJ mice (strain # 002448) were purchased from Jackson Laboratories. Mice were housed in a barrier facility operated under standard 12 h light/12 h dark cycle (referred to as normal L/D) with the luminance ranging from 60 to 100 lux during the daily/light cycle.…”
Section: Methodsmentioning
confidence: 99%